PERAN BIMBINGAN BELAJAR DALAM PEMBENTUKAN SIKAP KEMANDIRIAN SISWA SDN 2 WARUGEDE - Arief Hidayat Afendi; Siti Inayah; Diana Setiana (PGSD Universitas Muhammadiyah Cirebon, 2022)
ABSTRACT The purpose of this study is to determine the tutoring by the teacher to the students of SDN 2 Warugede, and to know the role of tutoring in the formation of the attitude of independence of the students of SDN 2 Warugede. Answering the objectives of the research above, the researcher uses a qualitative research approach with a special type of study, the instruments used are interviews, observations, and documentation. As well as data analysis techniques using data collection, data reduction, display data, and drawing conclusions.The results of the study can be concluded that routine tutoring is carried by teachers after coming home from school through the efforts made including: providing effective ways of learning, determining student study groups, holding meetings with parents of students, conducting repair teaching, conducting enrichment teaching, increasing student learning motivation, improving student skills, as well as improving student attitudes and good habits. Provide tutoring to students who are slow and fast learners, so that there is a change in the attitude of independence of the students of SDN 2 Warugede which can be seen from the initiative, responsibility, self-confidence, and self-control of students. Thus, tutoring can play a role in shaping the attitude of independence of the students of SDN 2 Warugede. Keywords: Tutoring, Independence Attitude. ABSTRAK Tujuan penelitian ini yaitu untuk mengetahui bimbingan belajar oleh guru kepada siswa SDN 2 Warugede, dan mengetahui peran bimbingan belajar dalam pembentukan sikap kemandirian siswa SDN 2 Warugede. Menjawab tujuan tersebut penelitian di atas peneliti menggunakan metode pendekatan penelitian kualitatif dengan jenis studi khasus, instrumen yang digunakan wawancara, observasi, dan dokumentasi. Serta teknik analisis data menggunakan pengumpulan data, reduksi data, data display, dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa bimbingan belajar rutin yang dilakukan oleh guru setelah pulang sekolah melalui upaya yang dilakukan diantaranya: memberikan cara-cara belajar yang efektif, menentukan kelompok belajar siswa, mengadakan pertemuan dengan orang tua siswa, mengadakan pengajaran perbaikan, mengadakan pengajaran pengayaan, peningkatan motivasi belajar siswa, peningkatan keterampilan siswa, serta peningkatan sikap dan kebiasaan siswa yang baik. Memberikan bimbingan belajar kepada siswa yang lambat dan yang cepat belajar, sehingga adanya perubahan kepada sikap kemandirian siswa SDN 2 Warugede yang terlihat dari inisiatif, tanggungjawab, percaya diri, dan kontrol diri siswa. Kata Kunci: Bimbingan Belajar, Sikap Kemandirian.